From cover to Editorial - Syed Ahmad, Sharifah Suhanah (Journal of Malaysian and Comparative Law, 2021)
<span data-sheets-value="{"1":2,"2":"Our June 2020 edition of the JMCL kicks off with Jaspal Kaur’s analytical discourse on the Malaysian Federal Court’s decision in the case of Public Prosecutor v Azmi bin Sharom. In “Free Speech, Constitutional Interpretation and Sedition in Malaysia: Taking a Rights Expansive Approach”, the author examines how the Federal Court tested the constitutionality of the Sedition Act 1948 by interpreting the clauses of article 10 of the Federal Constitution, in particular the approaches to constitutional interpretation adopted by the Courts.\r In “Suppressing . . . "}" data-sheets-userformat="{"2":5085,"3":{"1":0},"5":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"7":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"10":1,"11":0,"12":0,"15":"Arial"}">Our June 2020 edition of the JMCL kicks off with Jaspal Kaur’s analytical discourse on the Malaysian Federal Court’s decision in the case of Public Prosecutor v Azmi bin Sharom. In “Free Speech, Constitutional Interpretation and Sedition in Malaysia: Taking a Rights Expansive Approach”, the author examines how the Federal Court tested the constitutionality of the Sedition Act 1948 by interpreting the clauses of article 10 of the Federal Constitution, in particular the approaches to constitutional interpretation adopted by the Courts. In “Suppressing . . .